Traffic Quality and its Management in Urban Areas - Csaba Koren (Communications - Scientific letters of the University of Zilina, 1999)
The purpose of the paper is to overview the status of traffic quality in various countries, based on a specific questionnaire and some literature survey by trying to give answers to the following questions: What is traffic quality? What is the level of traffic quality? Where is the quality gap? How is traffic quality managed? To collect information on these issues a questionnaire was established and members of the PIARC Committee on Urban Areas or technical experts indicated by them were approached. Also general information was collected regarding the cities involved. There were 32 cities from 16 countries that replied to the questionnaire.